"Okay, I will say in Korean and then in American": Translanguaging practices in bilingual homes. (March 2016) - Song, Kwangok
Building on the research on translanguaging practices in classrooms (e.g.García, 2009 ;Sayer, 2011 ) and immigrant families' literacy practices (e.g. Gregory et al., 2004;Li, 2006 ), this qualitative study explores the nature of translanguaging practices of four Korean bilingual children and their families in home literacy events. Participant observation with video recordings and field notes was used to gather data, and the data analysis focused on the literacy events defined byHeath (1982) and types of language use. The findings demonstrated that bilingual children and their family members used their two languages flexibly and strategically to create and negotiate meaning. Using both languages contributed to clarifying meaning in communication and expanding children's linguistic repertoires in their heritage language as well as in English. This study takes a particularized look at bilingual children's language experience in out-of-school contexts by focusing on families' ways of using their two languages to support their children's heritage language development in literacy events.